2013
DOI: 10.4103/0253-7176.122219
|View full text |Cite
|
Sign up to set email alerts
|

Dhat Syndrome: A Review of the World Literature

Abstract: Dhat syndrome is described as a culture bound syndrome (CBS). There is an ongoing debate on the nosological status of CBS. Dhat syndrome has been found to be prevalent in different geographical regions of the world. It has been described in literature from China, Europe, Americas, and Russia at different points of time in history. Mention of semen as a “soul substance” could be found in the works of Galen and Aristotle who have explained the physical and psychological features associated with its loss. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 35 publications
1
31
1
Order By: Relevance
“…[ 1 2 3 4 5 6 ] In general these studies suggest that patients with Dhat syndrome present with neurasthenic symptoms in the form of multiple somatic and psychological complaints, which they attribute to the passage of “Dhat.” The commonly reported symptoms include body aches, burning micturition, increased frequency of micturition, difficulty in micturition and hypochondriasis. [ 7 ] Many patients have comorbid psychiatric disorders; depressive and anxiety disorders being the most commonly reported symptoms. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 2 3 4 5 6 ] In general these studies suggest that patients with Dhat syndrome present with neurasthenic symptoms in the form of multiple somatic and psychological complaints, which they attribute to the passage of “Dhat.” The commonly reported symptoms include body aches, burning micturition, increased frequency of micturition, difficulty in micturition and hypochondriasis. [ 7 ] Many patients have comorbid psychiatric disorders; depressive and anxiety disorders being the most commonly reported symptoms. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] Many patients have comorbid psychiatric disorders; depressive and anxiety disorders being the most commonly reported symptoms. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…Although the pathways to care for patients with various psychiatric disorders and even psychosexual disorders have been studied across the world including India,[12131617181920212223242526] none of the study has evaluated the pathways of care of patients with Dhat syndrome. [26] Therefore, this study was planned to evaluate the pathway to care among patients with Dhat syndrome.…”
mentioning
confidence: 99%
“…[26] Therefore, this study was planned to evaluate the pathway to care among patients with Dhat syndrome.…”
mentioning
confidence: 99%
“…However, compulsive masturbation on a daily basis may create a dependency on it (Alsughier, 2015). It may also lead to mental disorders due to cultural and religious guilt (Gerressu et al, 2007;Davidson & Moore, 1994;Balhara & Deb, 2013), although this association is unexplained and may be a statistical coincidence. Carvalheira, Traeen and Stulhofer (2015) reported that persons who suffer from higher levels of sexual boredom masturbated at least several times weekly.…”
Section: Discussionmentioning
confidence: 99%